Penggunaan Pasir Alam Dalam Campuran Beraspal jenis AC - WC Dengan Pengujian Marshall Berdasarkan Sfesifikasi Bina Marga Tahun 2010 - Domel, Imam Islami; Sentosa, Leo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The use of natural sand as fine aggregate in AC (Asphalt Concrate) mixture is limited to a minimum value of 15% of total of mixture weight as stated by Bina Marga Spesification 2010. Evaluation from the aspect of utilization cost shows that natural sand is cheaper than fine aggregate from stone crushing process because of no extra cost for crushing. This research aimed to identify the optimum sand content that can be used at fine graded AC/WC mixture. The variation used in this research are 0%, 5%, 10%, 15%, 20%, 25% and 30% of total aggregate mixture. The addition of natural sand makes optimum bitumen content (OBC) will decrease. OBC for natural sand of 0% is 6,4 %, OBC for natural sand of 5% is 6,35 %, OBC for natural sand of 10% is 6,3 %, OBC for natural sand of 15% is 6,25 %, OBC for natural sand of 20% is 6,2 %, OBC for natural sand of 25% is 6,2 % while the OBC for natural sand of 30% is 6,15 %. Optimum natural sand content for asphalt mix AC/WC type is 15% with OBC of 6,25%. With no consideration in the maximum requirement of the use of 15% natural sand in Bina Marga Spesification 2010 natural sand still can be used up to 25% in AC/WC asphalt concrete mixture.  Keywords: natural sand, asphalt concrete AC / WC, Bina Marga Spesification 2010 and Marshall characteristic.